ANALISIS PENERAPAN PRINSIP GOOD GOVERNANCE DALAM PELAYANAN PUBLIK ADMINISTRASI KEPENDUDUKAN - Firda Yasmine Ardiani; Nur Handayani (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2026)
This study aims to assess the quality of population administration services and the implementation of good governance principles at the Gubeng Subdistrict Office, Surabaya. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The informants in this study consisted of the head of the governance and public service section, one service staff member, and two service users. The results show that service quality has met the main dimensions, namely empathy, assurance, reliability, tangibles, and responsiveness. In addition, good governance principles such as transparency, accountability, responsiveness, effectiveness, fairness, consensus orientation, strategic vision, and adherence to the rule of law have been implemented fairly well. However, there are still challenges in improving the understanding of both employees and the community regarding these principles. Therefore, continuous training and socialization programs are needed to improve service quality and strengthen the implementation of good governance.